Pengaruh Media Sosial Terhadap Karakter Kemandirian Belajar Mahasiswa Universitas Veteran Bangun Nusantara - Windrati Windrati; Suyahman Suyahman; Siti Fatimah (Universitas Negeri Padang, 2023)
Everyone must have a social media account and actively operate it, including students at the Bangun Nusantara Veterans University. Related to the current conditions, especially in the field of education, social media provides convenience and benefits for students, in addition to the negative effects of social media. This study aims to determine the effect of social media on the character of learning independence in students at Veteran Bangun Nusantara University. The type of research used in this study is descriptive qualitative with the object of research being the effect of social media on the character of independence, and the research subjects are students of Veteran Bangun University. Nusantara with a total of 10 students from semesters 2, 4, 6, and 8. The method of collecting data in this study used observation, interviews, and documentation. Then the data analysis technique used is the triangulation method by combining the results of interviews and observations made to obtain research results which are then described to explain the effect of social media on the character of student learning independence. This study found that social media has a positive influence on the ability and motivation to study independently for students at Veteran Bangun Nusantara University, with the consequence that students have difficulty managing time in their daily activities. With their good and bad experiences in using social media, it will help increase their independence, creativity, and confidence as human beings.